Effect of Kinetin and NAA on Regeneration of Carnation (Dianthus caryophyllus L.) from Shoot-tip Explants - Maitra, S.; Roychowdhury, N.; Ghosh, P. D.; Satya, P. (International Journal of Bio-resource and Stress Management, 2011)
Optimization of in-vitro culture condition of carnation bears high commercial interest for which identification of suitable regenerating media is an essential component. An experiment was undertaken involving 14 different regeneration media to identify effective media composition to get carnation plantlets in-vitro from shoot-tip explants. Results from two consecutive years revealed that msmedium supplemented with NAA (1 mg L-1) + Kinetin (2.5 mg L-1) and NAA (1 mg L-1) + Kinetin (3.5 mg L-1) were equally effective for production of proliferating cultures (99.45%) whereas response to other media were not satisfactory. A composition of MS medium supplemented with NAA (0.5 mg L-1) + Kinetin (0.5 mg L-1) and NAA (1 mg L-1) + Kinetin (0.5 mg L-1) showed inhibitory effect on proliferation. Earliest sign of proliferation (3.97 days) was noticed using a culture medium containing NAA (1 mg L-1) and Kinetin (2.5 mg L-1). Explants cultured on the same medium also produced longest shoots (6.60 cm) and highest number of average leaves culture-1 (33.07). Maximum number of shoots culture-1 (6.73) was obtained from the explants cultured on MS medium supplemented with NAA (1 mg L-1) and Kinetin (3.5 mg L-1). A study on root induction of regenerated shoots of carnation revealed that MS medium supplemented with IBA (4 mg L-1) + NAA (1 mg L-1) is the most effective rooting medium among four different media compositions, imparting rooting of 98.20% shoots and hence may be utilized for better root induction of carnation explants in-vitro.